Purchase order for soil test in the Brac University new campus site in different location along the boundary wall alignment - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and Z.E.C. Soil Test for soil test in the Brac University new campus site in different location along the boundary wall alignment for Brac University new campus project.